9 Year Compulsory Education Evaluation In Bojonegoro Regency, East Java Province, Indonesia. Year 2015 - ., Rupiarsieh (Advances in Social Sciences Research Journal, 2019)
Indonesia’s 1945 Constitution, Article 31, Sentence 1, stipulates that “each citizen has the right to education.” This means that the Indonesian government has the obligation to provide and run a national education system, in order to make intelligent the nation. Then, described in 2003 Law number 20 on National Education System and in 2008 Government Regulation Number 47, on Compulsory Education, that stipulated the Government and Local Government guarantee the execution of compulsory education at the least in basic education without charging any tuition fee; and obligates each region to set up Local Regulation and implement the Basic Compulsory Education Program. The Bojonegroro Regency Regulation Number 4 Year 2012, Article 65, Sentence 1, letter (a) states that: “the Local Government is obligated to set a 12 (twelve) year compulsory education, which comprises of 9 (nine) year basic education and 3 (three) year middle education.” It guarantees that each child has access to at the least 9 years of education, and that 9 year basic education expenses is provided for. The evaluation of the 9 year compulsory education in Bojonegero, shows that the average length of education is 6.7 years. It means that the citizen of Bojonegoro having finished the 6 year Elementary School. The aim of 9 year compulsory education hasn’t been reached. Using the qualitative descriptive method, show several causal factors. These factors are that school participation is low, there is significant level of illiteracy and school drop outs, and the psychology of rural people who think that to ease the parents’ burden, after 6 years of Elementary school the girls are married off and the boys help with earning money. To reach the aim of 9 year compulsory education, there should be a special program to eradicate illiteracy, raising the capacity of Kejar Program A and B, Back to School Movement, and Education Policy that involves both formal and non-formal education.